Efeito farmacológico do disseleneto de m-trifluormetil-fenila na comorbidade entre dor e depressão em camundongos - Brüning, César Augusto (2015)
Chronic pain and depression often coexist, and several mechanisms are involved in the pathogenesis of this comorbidity, which confer it resistance to treatment. The serotonergic system is considered a central mechanism in the pain-depression dyad, which could also be generated from dysfunctions in the immune system or injuries to neuronal tissue, involving the process of neuroinflammation. The organoselenium compound m-trifluoromethyl-diphenyl diselenide (m-CF3-PhSe)2 shows antinociceptive and antidepressant-like effects in acute models in mice and behavioral evidence demonstrated that its antidepressant-like effect is related to the serotonergic system. The aim of this study was to further characterize the pharmacological effects of (m-CF3-PhSe)2 and investigate its effect on the comorbidity between pain and depression in mice, addressing the pathogenic mechanisms of this condition. The research project was approved by the ethics committee (CEUA) of the Federal University of Santa Maria (042/2012). First, it was demonstrated that the serotonergic system is involved in the antinociceptive effect of (m-CF3-PhSe)2 (1 50 mg/kg, p.o.) in the glutamate test, once antagonists of serotonergic receptors 5-HT1A (WAY100635) and 5-HT2A/2C (ritanserin) blocked its effect. In addition, (m-CF3-PhSe)2 (10 and 50 mg/kg, p.o.) inhibited the serotonin (5-HT) reuptake ex vivo in synaptosomes. It was also assessed the selenium distribution at different time points after the administration of (m-CF3-PhSe)2 (500 mg/kg, p.o.), which demonstrated a wide distribution in different tissues, including the brain. Taking into account that inflammation could be closely related to depression, the effect of (m-CF3-PhSe)2 on the depressive-like behavior induced by intracerebroventricular (i.c.v.) injection of tumor necrosis-α (TNF-α) in the forced swimming test (FST) and tail suspension test (TST) was also evaluated. The acute treatment with (m-CF3-PhSe)2 (from 0.1 mg/kg) at low doses prevented the increase in the immobility time of animals, which is an indicative of depressive-like behavior, in both tests, without altering the locomotor activity of mice. The doses that were not effective (0.01 mg/kg in the FST and 0.1 mg/kg in the TSC) in the acute treatment blocked the effect of TNF-α when chronically administered for 2 weeks to mice. In addition, (m-CF3-PhSe)2 demonstrated an anti-inflammatory effect in both acute and subchronic treatments, preventing the activation of p38 mitogen-activated protein kinase (p38 MAPK) and the increase of nuclear factor-κB (NF-κB) levels induced by TNF-α in the hippocampus and pre-frontal cortex of mice. Lastly, it was demonstrated that (m-CF3-PhSe)2 (1 and 10 mg/kg, i.g.) elicited antinociceptive and antidepressant-like effects in a model of pain and depression comorbidity induced by partial sciatic nerve ligation (PSNL) in mice, which was related to anti-inflammatory effect. PSNL induced mechanical allodynia observed in the Von- frey hair test and increased the immobility time of animals in the FST and (m-CF3-PhSe)2 in both acute and subchronic treatments at low doses was effective in blocking these alterations. PSNL also induced an increase of pro-inflammatory cytokines in serum, cerebral cortex and hippocampus of mice. An increase of adrenocorticotropic hormone (ACTH) and corticosterone in the serum, activation of p38 MAPK, an increase in the NF-κB and cyclooxygenase-2 (COX-2) levels, a decrease of brain-derived neurotrophic factor (BDNF) levels and an increase of 5-HT reuptake and glutamate release in the cortex and hippocampus of mice were found in PSNL mice. In a general way, both acute (10 mg/kg, i.g.) and subchronic (0.1 mg/kg, i.g.) (m-CF3-PhSe)2 treatments were effective in preventing these alterations, although the best results were observed in the subchronic treatment. Considering that pain-depression dyad is a multi-pathogenic condition and inflammation could have a central role in this comorbidity, (m-CF3-PhSe)2 might be considered an interesting therapeutic alternative to treat chronic pain associated with depression.